Study on the Effect of Pre-harvest Fruit Bagging for Enhancing Fruit Quality in Mango cv. Baneshan - Rani, K. Radha; Rajyalaksmi, R.; Lakshmi, B. K. M.; Sravanthi, G.; Shaliraju, G. (International Journal of Economic Plants, 2025)
The experiment was conducted during March–June, 2021 to 2024 at Mango Research Station, Nuzvid, Dr. YSR Horticultural University, Andhra Pradesh, India to study the impact of bagging on fruit quality and pest and disease control. The experiment was laid out in RBD with 3 replications and 7 treatments of different coloured bags with and without transparent flip on bags. The fruits were bagged approximately at 100 g weight of the fruit uniformly in all treatments. Harvesting of the bagged fruits were done after 65 days of bagging along with bags and kept for ripening after removal of bags. After fully ripening of fruits the analysis was done for quality parameters. The results revealed that reddish brown bags were superior for average fruit weight (365.8 g), ascorbic acid (42.3 mg 100 g-1), and total sugars (22.7%), followed by yellow and white bags. Thrips and sooty mould damage were recorded as minimum (8.67% 14.27, respectively) in reddish brown bags. Fruit fly damage was nil in bagged fruits, while the control recorded 42.33%. However, there was no significant difference observed between with flip and without flip within the same colour of bags for most of the quality parameters. Based on these results, pre-harvest bagging of fruits with reddish brown or yellow colour can be recommended to improve the fruit quality and to avoid pests and disease incidence, thereby reducing pesticide residues in mango to increase the exports.